2020
DOI: 10.1002/brb3.1620
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular MRI: A valuable tool to detect cardiac source of emboli in cryptogenic ischemic strokes

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Among 6 MR studies, 8 , 9 , 17 , 28 , 48 , 49 5 reported when patients were imaged (within 24 hours 9 to 1 week 49 of symptom onset). Four studies imaged at 3 Tesla, 8 , 9 , 28 , 48 1 at 1.5 Tesla 49 , and 1 used both 1.5 and 3 Tesla 17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 6 MR studies, 8 , 9 , 17 , 28 , 48 , 49 5 reported when patients were imaged (within 24 hours 9 to 1 week 49 of symptom onset). Four studies imaged at 3 Tesla, 8 , 9 , 28 , 48 1 at 1.5 Tesla 49 , and 1 used both 1.5 and 3 Tesla 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Among 6 MR studies, 8 , 9 , 17 , 28 , 48 , 49 5 reported when patients were imaged (within 24 hours 9 to 1 week 49 of symptom onset). Four studies imaged at 3 Tesla, 8 , 9 , 28 , 48 1 at 1.5 Tesla 49 , and 1 used both 1.5 and 3 Tesla 17 . Techniques included 4‐dimensional flow to assess extent of retrograde aortic blood flow, 9 , 48 aortic vessel wall/plaque signal, 9 , 17 , 28 , 48 , 49 Cine of plaques ≥4 mm to detect mobile plaque components, 28 and aortic lumenography with contrast‐enhanced or dynamic time‐resolved magnetic resonance angiography with interleaved stochastic trajectories techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Other modalities such as nonobstructive general angioscopy have the possibility to detect aortic plaques in the aortic arch more accurately than TEE and might help to diagnose atheromatous plaques and embolic materials in the distal ascending aorta which could not be detected on TEE, 15 however nonobstructive general angioscopy is an invasive procedure and the technique still require further evaluation regarding its feasibility. Other cardiovascular images such as CT angiography 16 or MRI 17 are also useful for detecting embolic sources including aortic atherosclerosis. CT angiography is useful for detecting plaque location, size, calcification with contrast, but is less appropriate for patients with renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no gold standard for the diagnosis of ASA. It has been found that the local tumor-like projection towards a atrium ≥10 mm in the middle of the atrial septum is more suitable for the diagnosis of ASA [11][12] . The occurrence of ASA may be due to the pressure difference between the left and right atrium, or may be due to the weak development of fibrous connective tissue in the oval atrial septum, which leads to the lateral expansion of the atrial septum with low pressure [13][14] .…”
Section: Discussionmentioning
confidence: 99%